Advancing Research Methodologies in Management: Revisiting Debates, Setting New Grounds for Pluralism - Christofi, Michael; Hadjielias, Elias; Hughes, Mathew; Plakoyiannaki, Emmanuella (My University, 2024)
The purpose of this introduction and Special Issue (SI) is to offer a unique and timely opportunity to explore, revisit and critically examine key methodological debates and tensions with the purpose of advancing diversity and novel theorizing in the field. We join voices with the authors of the five papers of this SI to problematize taken-for-granted assumptions and research traditions and pave the way for inclusive and novel theorizing in management scholarship. We revisit four long-lasting debates that hinder methodological pluralism and diversity in management scholarship: (a) the quantitative-qualitative research divide, (b) the legitimacy of mixed-methods research, (c) the rigour versus relevance tension and (d) the lack of methodological innovation. We suggest that these debates are at least partly counterproductive because they create silos and opposing camps, thereby inhibiting an appreciation of different worldviews and collective learning. The dominance of functionalism and positivism in quantitative research and the inappropriate transfer of quantitative logics in qualitative research have led to a lack of diversity in empirical methodologies. The field's limited methodological diversity is further proliferated by a strict adherence to quality standards that have inadvertently promoted homogeneity. This introduction highlights the challenges and potential of mixed methods, which are gaining momentum owing to calls for methodological pluralism. We also call for a re-evaluation of quality standards to encourage more innovative and diverse research methodologies.
Keywords: Μanagement scholarship; Mixed methods research; Methodology; Qualitative methods